Peran Keluarga Berhubungan dengan Tumbuh Kembang Anak Usia Pra Sekolah - Suprayitno, Emdat; Yasin, Zakiyah; Kurniati, Dian; Rasyidah, Rasyidah (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2021)
Pre-school age is a golden age where children’s growth and development affects the future therefore at this time it is important to pay attention so that the child’s growth and development runs optimally. The role of the family is one of the determining factors for child development because the family is the closest individual and influences the child’s growth and development.This research design is quantitative with using analytical observational. The respondents in this study were families who had pre-school age children. The sampling technique uses a random sampling of 54 people. The independent variable is a family role, whereas the dependent variabel is growth and development of pre-school age children. The data collection is starting with questionnaires. The data is analyzed using chi square. The results showed that there was a relationship between the role of the family and the growth and development of pre-school age children (0,000)<(0,05).The conclusion of this study is that there is a relationship between the role of the family and the growth and development of pre-school children at TK Al Amanah in the village of Campor Barat. Based on the results of this study, it is hoped that families will pay more attention to the growth and development of children at pre-school age. and health workers can provide counseling to families of pre-school age children regarding the role of the family in the child's growth and development process so that it runs optimally.